Preparation of underwater superoleophobic porous coating via a co‐deposition method for oil/water mixture separation. Issue 10 (10th August 2022) - Duan, Yanping; Dong, Guangli; Wu, Ruijie; Zhao, Xia; Li, Mingwei; Zhang, Fengfeng; Song, Zhimin; Hao, Hong
Abstract: Oil contamination is problematic in subaqueous environments. Here, a cationic poly(N, N‐dimethyl‐N‐(ethoxycarbonylmethyl)‐N‐[2′‐(methacryloyloxy)ethyl]‐ ammonium chloride) (PCBMAE) was synthesized, and a one‐step approach of dopamine‐assisted codeposition was used to generate PCBMAE/polydopamine (PDA) superhydrophilic and underwater superoleophobic coatings coated on a stainless steel mesh for oil/water separation. The structures, surface morphologies, and properties of the coatings were analyzed by IR, SEM, TGA, and contact angle measurements. During deposition at a PCBMAE and DA mass ratio of 1:1, PCBMAE/PDA mixture particles uniformly adhered to the skeletons of the mesh, increased the surface roughness, created enriched surface micro/nanostructures, and reduced the surface energy of the coating. This endowed the metal mesh with superhydrophilicity and underwater superoleophobicity (oil contact angle 163°) without blocking the mesh, and the deposition density was 0.26 mg/cm 2 . The separation efficiency of the coated mesh was 99.6% for the first castor oil/water separation and dropped to 98.0% after 5 cycles. After 25 cycles, the separation efficiency was still higher than 95%. The PCBMAE/PDA codeposited mesh exhibited high oil/water separation efficiency, stable mechanical properties, and weather stability under different harsh environments, making it a promising separation material for future industrial applications. Abstract : Oil contamination is problematic in subaqueous environments. Here, a cationic poly(N, N‐dimethyl‐N‐(ethoxycarbonylmethyl)‐N‐[2'‐(methacryloyloxy)ethyl]‐ ammonium chloride) (PCBMAE) was synthesized, and a one‐step approach of dopamine‐assisted codeposition was used to generate PCBMAE/polydopamine (PDA) superhydrophilic and underwater superoleophobic coatings coated on a stainless steel mesh for oil/water separation.This endowed the metal mesh with superhydrophilicity and underwater superoleophobicity (oil contact angle 163°) without blocking the mesh, and the deposition density was 0.26mg/cm 2 . The separation efficiency of the coated mesh was 99.6% for the first castor oil/water separation and dropped to 98.0 % after 5 cycles. After 25 cycles, the separation efficiency was still higher than 95%.